Binding abilities of polyaminocyclodextrins: polarimetric investigations and biological assays - Russo, Marco; La Corte, Daniele; Pisciotta, Annalisa; Riela, Serena; Alduina, Rosa; Lo Meo, Paolo (Beilstein Journal of Organic Chemistry, 2017)
Three polyaminocyclodextrin materials, obtained by direct reaction between heptakis(6-deoxy-6-iodo)-β-cyclodextrin and the proper linear polyamines, were investigated for their binding properties, in order to assess their potential applications in biological systems, such as vectors for simultaneous drug and gene cellular uptake or alternatively for the protection of macromolecules. In particular, we exploited polarimetry to test their interaction with some model p-nitroaniline derivatives, chosen as probe guests. The data obtained indicate that binding inside the host cavity is mainly affected by interplay between Coulomb interactions and conformational restraints. Moreover, simultaneous interaction of the cationic polyamine pendant bush at the primary rim was positively assessed. Insights on quantitative aspects of the interaction between our materials and polyanions were investigated by studying the binding with sodium alginate. Finally, the complexation abilities of the same materials towards polynucleotides were assessed by studying their interaction with the model plasmid pUC19. Our results positively highlight the ability of our materials to exploit both the cavity and the polycationic branches, thus functioning as bimodal ligands.
Keywords: aminocyclodextrins; binding properties; nitroanilines; pDNA; polarimetry; supramolecular chemistry